The Production of Seaweed (Eucheuma cottonii) Jelly Candy with the Addition of Calabur Fruit Puree - Welhelmina R Notanubun; La Ega; Rachel Breemer (Universitas Pattimura, 2022)
his study aims to determine the appropriate concentration of calabur pulp for producing seaweed jelly candy with the best physicochemical and organoleptic characteristics. The study used a single factor completely randomized design (CRD) with 5 treatment levels and 2 replications. The treatment levels in this study were: P0 (without calabur), P1 (10% calabur), 20% (20% calabur), P3 (30% calabur), P4 (40% calabur). The results showed that the concentration of 40% calabur gave better chemical characteristics, namely moisture content of 48.33%, total sugar content of 51.04%, ash content 6.00%, vitamin C content of 0.05%, and yield of 65.31%. The jelly candy that the panelists preferred had a 30 calabur concentration, with a hedonic value of 3.24 on color (liked), 3.36 on taste (liked), 3.50 on aroma (liked), 3.24 on texture (liked), and 3.24 on overall (liked), and the hedonic quality of 3.20 on color (chocolate), 3.20 on taste (sweet), 3.44 on aroma (calabur flavored) and 3.40 on texture (chewy).